On the Practical Compensator Design of Time-Varying Perturbed Systems in Hilbert Spaces. (27th May 2022) - Damak, Hanen
Abstract: In this paper, we treat the problem of practical feedback stabilization for a class of nonlinear infinite-dimensional control systems by means of an observer. A compensator design is given under a restriction of the perturbed term that the perturbations is bounded by the sum of a Holder continuous function and a Lipschitz function where the nominal system is supposed to be exponentially stabilizable by a linear feedback. The results are illustrated with an example.